HUMOUR GENRE IN ENGLISH AND UZBEK LITERATURE - Rakhimova Durdona (Western European Studies, 2024)
This article examines the humour genre in English and Uzbek literature, focusing on the similarities and differences between the two. The study employs a comparative analysis approach, reviewing relevant literature and analyzing selected works from both languages. The results reveal that while both English and Uzbek literature share common themes and techniques in humour, there are distinct cultural influences that shape their respective humour genres. The analysis highlights the use of irony, satire, and wordplay in both languages, as well as the impact of historical and social contexts on the development of humour.
Keywords: humour; English literature; Uzbek literature